2019
DOI: 10.1073/pnas.1817202116
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetries between achromatic and chromatic extraction of 3D motion signals

Abstract: Motion in depth (MID) can be cued by high-resolution changes in binocular disparity over time (CD), and low-resolution interocular velocity differences (IOVD). Computational differences between these two mechanisms suggest that they may be implemented in visual pathways with different spatial and temporal resolutions. Here, we used fMRI to examine how achromatic and S-cone signals contribute to human MID perception. Both CD and IOVD stimuli evoked responses in a widespread network that included early visual ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 111 publications
1
21
0
Order By: Relevance
“…However, this study did not investigate activations in regions anterior to the hMT+ complex. More recently, Kaestner et al (2019) confirmed that the hMT+ complex and two groups of ROIs that respectively gathered dorsal (V3A/B and IPS-0) and ventral (V4, LO-1 and LO-2) areas were more responsive to CDOT than to a control condition where the temporal frames were scrambled. These authors also found significant responses to CDOT in the CSM area but that were not as pronounced as those measured in hMT+.…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…However, this study did not investigate activations in regions anterior to the hMT+ complex. More recently, Kaestner et al (2019) confirmed that the hMT+ complex and two groups of ROIs that respectively gathered dorsal (V3A/B and IPS-0) and ventral (V4, LO-1 and LO-2) areas were more responsive to CDOT than to a control condition where the temporal frames were scrambled. These authors also found significant responses to CDOT in the CSM area but that were not as pronounced as those measured in hMT+.…”
Section: Introductionmentioning
confidence: 78%
“…In the present study, we performed fMRI recordings in awake behaving macaques to identify the cortical regions sensitive to motion-in-depth defined by changing disparity over time (CDOT). To facilitate the comparison with previous human data, we used an experimental protocol that was directly inspired from the neuroimaging studies described above (Likova and Tyler 2007;Rokers et al 2009;Kaestner et al 2019). In order to precisely determine the limits of the MT cluster, we ran an additional retinotopic mapping experiment that permitted to delineate its four constituting areas V4t, MT, MSTv, and FST (Kolster et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…An example of a single frame from the stimulus is presented in Figure 2. Animated examples of CD and IOVD stimuli are available in Supplementary Materials of previous work (Kaestner et al, 2019). Figure 2.…”
Section: Stimuli CD and Iovd Stimulimentioning
confidence: 99%
“…The stimuli were similar to those used in previous papers (Maloney et al, 2018;Kaestner et al, 2019). Briefly, MID stimuli consisted of random dot patterns that were designed to experimentally dissociate CD-or IOVD-based mechanisms.…”
Section: And Iovd Stimulimentioning
confidence: 99%
“…One possibility is the existence of a mechanism that is agnostic to differences in CD and IOVD cue properties, or possibly fuses both velocity and disparity signals together (Movshon and Newsome, 1996;Ponce et al, 2008). One candidate cortical location for this general stereomotion processing mechanism is the region in or around the human MT+ complex which includes cells that are known to be sensitive to both lateral motion defined from a variety of cues, as well as 3D-motion (Likova and Tyler, 2007;Rokers et al, 2009;Huk, 2012;Czuba et al, 2014;Sanada and DeAngelis, 2014;Kaestner et al, 2019;Héjja-Brichard et al, 2020). The temporal integration of 3D-motion signals has been shown to occur across hundreds of milliseconds, from ∼150 to 1000 ms post-stimulus, with sensitivity to 3Dmotion increasing across this integration period (Katz et al, 2015) and the behavioral integration of 3D-motion signals across time is known to be relatively slow (when compared to lateral motion) (Richards, 1972;Norcia and Tyler, 1984;Watamaniuk, 1995, 1996;Stone, 2004, 2006;Harris et al, 2008;Huk, 2012).…”
Section: Cross Trained Decoding At Late Stages Of the Eeg Time Coursementioning
confidence: 99%